H. W. Sayre correspondence - Sayre, H. W.
ALS written by Sayre relating to an order for the Asbestos Felting Company, New York, N.Y., of which he was superintendent.
Businessman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Asbestos Felting Company; Asbestos industry -- New York (State) -- New York; Businessmen